Preschool overweight and obesity in urban and rural Vietnam: differences in prevalence and associated factors - Loan Minh Do; Toan Khanh Tran; Bo Eriksson; Max Petzold; Chuc T. K. Nguyen; Henry Ascher (Taylor & Francis Group, 2015)
Background: Childhood obesity may soon be an equally important health threat as undernutrition and infectious diseases. Accurate information about prevalence and risk factors of obesity in children is important for the design of prevention. Objective: The aim of this study was to estimate prevalence of overweight and obesity for preschool children in two Vietnamese areas, one urban and one rural, and to identify risk factors. Design: A cross-sectional study was conducted in urban Dong Da and rural Ba Vi districts, Hanoi, Vietnam. Totally, 2,677 children, 1,364 urban and 1,313 rural, were weighed and measured. Caregivers were interviewed. Background information about children and families was obtained from regular household surveys. Results: The prevalence of overweight and obesity combined were 21.1% (95% CI 18.9-23.3) in the urban area and 7.6% (95% CI 6.2-9.2) in the rural. Multiple logistic regression revealed that at the individual level, in both sites, the risk increased with increased child age. The identified urban risk factors were being a boy, consuming large amounts of food, eating fast, and indoor activity less than 2 hours per day. The rural risk factors were frequent consumption of fatty food. At the family level, significant association was found in rural areas with frequent watching of food advertisements on television. Conclusions: Overweight and obesity are emerging problems in Vietnam, particularly in the urban context. Prevention programs should focus on education about healthy eating habits at early preschool age and need to be tailored separately for urban and rural areas since the risk factors differ. Non-healthy food advertisement needs to be restricted.